1948
DOI: 10.1021/ja01186a523
|View full text |Cite
|
Sign up to set email alerts
|

A Crystalline Factor Functionally Related to Folic Acid

Abstract: Communications to the Editor 2299 (m. p. 135°) and a dipicrate (m. p. 206-207°) of ¿¿-sparteine, which they obtained from naturally occurring ¿¿-lupanine. As a further proof of identity, our ¿¿-sparteine was converted to dloxysparteine, m. p. 110-111°, by treatment with alkaline potassium ferricyanide. The melting point of ¿¿-oxysparteine has been reported as 110-111°,6 112-113°,4 1130.7 Finally, the infrared absorption spectra of our synthetic ¿¿-sparteine dipicrate and an authentic sample of ¿-sparteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1949
1949
1957
1957

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The work of Lampen & Jones (1946 and of Woods (1948) points in the same direction. The observation of Shive et al (1948) that thymidine may be the end product of this reaction further confirms this hypothesis. Thymidine is required by a number of lactobacilli which formerly could not be grown on simple synthetic media (Snell, Kitay & McNutt, 1948).…”
Section: Inhibition Of Xanthine Oxidase By 6-pteridylaldehydesupporting
confidence: 67%
See 1 more Smart Citation
“…The work of Lampen & Jones (1946 and of Woods (1948) points in the same direction. The observation of Shive et al (1948) that thymidine may be the end product of this reaction further confirms this hypothesis. Thymidine is required by a number of lactobacilli which formerly could not be grown on simple synthetic media (Snell, Kitay & McNutt, 1948).…”
Section: Inhibition Of Xanthine Oxidase By 6-pteridylaldehydesupporting
confidence: 67%
“…T h e action of methylfolic acid was counteracted by thymidine, the desoxyriboside of thymine. This led Shive, Eakin, Harding, Ravel & Sutherland (1948) to suggest that thymidine is the end substrate in the synthesis of which PGA is concerned as part of an enzyme system.…”
Section: Conference Proceedings I949mentioning
confidence: 99%
“…The fact that thymine is more effective than thymidine in overcoming the inhibitory effects of aminopterin and amino-an-fol on the growth and division of E. coli (strain B) is of interest. The nucleoside is usually considered to be more effective than the free pyrimidine base in counteracting the effects of folic acid deficiency and in reversing the effects of the analogues on bacterial growth (Shive et al, 1948;Martin, 1951). Indeed, Franklin et al (1949) found that thymine had no effect upon the growth-inhibitory action of aminopterin on their strain of E. coli, whereas reversal was obtained with thymidine.…”
Section: Cofimentioning
confidence: 99%
“…Thymine or thymidine has frequently been found to be a component of mixtures which will support the growth of organisms requiring members of the folic acid group in the absence of these factors. Shive, Eakin, Harding, Ravel & Sutherland (1948) found the inhibition of growth of a strain of Ln. mesenteroides by a methylpteroylglutamic acid to be overcome by thymidine, but not thymine, as well as by ptero ylglut amic acid.…”
Section: J Lascelles M J Cross and D D Woodsmentioning
confidence: 99%